Work Environment, Creativity and Innovation - Maharjan, Pushpa (PYC Nepal Journal of Management, 2011)
The paper examines the relationship between the work environment and employee creativity in the Nepalese banking sector using the survey method. The survey was conducted by distributing 112 sets of self-administered questionnaire to the respondent employees of four sample commercial banks. Of which, 86 respondents returned the completely filled questionnaires in usable form making the response rate of 77 per cent. The study concludes from the analysis of the data that organizational impediment does make adverse impact on employee creativity and innovation.